Conventional and Non-conventional Approach towards the Extraction of Bioorganic Phase - A Dharmaraj, Prof. Madya Dr. Saravanan (Springer International Publishing AG, 2018)
Natural products such as natural food are the richest bio-resource of bioorganic compounds for modern medicines, nutraceuticals, food supplements and pharmaceutical applications. The research and application on natural food started with the extraction techniques that play an important role to the extraction quantity (Yield), quality (extracted phytochemicals) and also to the subsequent analyses accomplished to evaluate the biological and chemicals activities. Various types of technologies with different principles of extraction of bioorganic compounds are available today. Based on the literature the conventional extraction methods show better recoveries of bioorganic substances of natural food. Also, conventional extraction methods facilitate the extraction of high concentration of bioorganic substances with the safe solvents system such as pure ethanol. Moreover, conventional extraction methods is still widely used due to its simplicity. However, the conventional extraction methods is not always suitable for industrial uses due to long extraction time and large consumption of harmful solvents systems such as methanol. Therefore, modern nonconventional extraction methods could be an alternative extraction method. Hence, in spite of good results achieved with the conventional extraction methods, modern non-conventional extraction methods was established to search for a faster and better extraction method consuming less solvent, especially those that are unattractive in food industry. This chapter is intended to provide insights on conventional and non-conventional extraction methods with their advantages and disadvantage or limitation. © Springer International Publishing AG, part of Springer Nature 2018.